The development and evaluation of a computer based e-learning tool to enhance knowledge of workplace wellness - Hamer, Naomi (2014)
Abstract The need to improve the quality of dementia care in the acute hospital setting has been made evident by concerns of poor patient outcomes and failure to achieve the desired standard of person-centred dementia care. Such poor outcomes may be associated with the apparent failure to prioritise the care of dementia patients in comparison to other areas of hospital-based care in recent years. Considering the fact that national prevalence of dementia is rising, it appears that to address concerns of the quality of dementia care may be fundamental for high quality future health care. Since the UK government has now embraced the need to improve the quality of dementia care and outlined intentions to increase funding and research in this area, the need for sufficient recognition and understanding of the barriers to person-centred dementia care is essential, in order to ensure funding is directed to areas that will help to improve dementia care. However, review of current literature highlights a need for further insight into the barriers to the provision of person-centred dementia care. This study therefore explored the barriers to person-centred dementia care through the conduction of 14 semi-structured interviews with nurses and healthcare assistants, recruited from six Health Care of the Elderly wards within a single NHS trust. Interviews examined participants’ perceptions and experiences of current standards of dementia care. Findings identified a wide range of factors that appeared to hinder staffs’ ability to provide person-centred dementia care, but suggested that there was a particular need for further dementia-specific knowledge and training, with specific regards to the need to raise awareness of the potential influence of social interaction on personhood and to adapt communication accordingly.